Experimental and numerical investigations on the development and optimization of latent heat storage system - Niyas U.S., Hakeem (My University, 2017)
Energy plays a major role for the existence of humanity. For a quite long period, much of the energy needs of the humankind are fulfilled from the non-renewable energy sources such as coal, oil and natural gas. The gruesome point of usage of non-renewable energy sources in the power generation, heating and cooling, and transportation sector is the greenhouse gas emissions, which has several adverse effects like climate change, global warming, ozone depletion, sea level rise, etc. Hence, several countries ramped their investments on renewable energy based technologies to combat these harmful environmental outcomes.Concentrated solar power (CSP) is one of the promising large-scale power generation technologies among the renewables, which is being widely commercialized now. The major problem that all solar power plants face is the intermittent solar radiation that can be solved by adding storage. Of all the storage options, thermal energy storage (TES) is the most economical, which gives an advantage to CSP plants over solar PV plants since TES can be integrated with CSP to ensure power 24/7. The TES systems are broadly classified into sensible heat storage, latent heat storage (LHS) and thermochemical heat storage. LHS systems using phase change materials (PCMs) are highly attractive due to their high volumetric heat storage capacity, compactness, moderate cost, near constant temperature heat storage/retrieval and adaptability over wider temperature ranges.
Muthukumar, P
Keywords: MECHANICAL ENGINEERING; MECHANICAL ENGINEERING